Extracto acuoso de Mansoa alliacea ajo sacha incluido en la dieta como estimulante en el crecimiento, desempeño productivo y composición bromatológica de alevinos de Colossoma macropomum gamitana - Zamudio Orbe, Pedro Angel (2023)
The present study investigated the effect of the aqueous extract of the Mansoa alliacea ajo sacha leaf on the growth, productive performance and bromatological composition of Colossoma macropomum fry. The research was carried out at the facilities of the Piscigranja Experimental Pilot Center - Quistococha UNAP, from September to November 2022. A total of 600 fingerlings were distributed in 12 pens of 50m2 (1 fish/m2) and fed for 90 days with balanced food enriched with aqueous extract of Mansoa alliacea (0 mL/kg, 4 mL/kg, 8 mL/kg and 12 mL/kg), with a frequency of 2 times a day and feeding rate of 6% (two months) and 3% (two months). two months). Every 15 days, the weight and length of the fry were recorded to determine growth in weight (g) and total length (cm) and zootechnical indices (daily weight gain, biomass gained, specific growth rate, apparent feed conversion index). and survival). Likewise, water quality parameters were monitored: temperature (C), transparency (cm), dissolved oxygen (mg/l), ammonium (mg/l) and pH (UI). At the end of the experiment (90 days) the hepatosomatic index and the bromatological composition (protein, fat and ash) of the muscles of the C. macropomum fry were determined. The results show that 12 mL/kg of the aqueous extract in the diet of C. macropomum increases weight growth (125g), daily weight gain (1.35 g/day), biomass gained (6095 g), specific growth rate (4.12% day) and improves the apparent feed conversion rates (1.42), also increases the percentage of protein and ash, and decreases fat in the muscle of the fry. There was no variation in water quality during the experiment. The aqueous extract of M. alliacea in the concentration of 12 mL/kg can be used as a growth stimulant, productive performance and bromatological composition of Colossoma macropomum fingerlings.